2016
DOI: 10.4054/mpidr-wp-2016-010
|View full text |Cite
|
Sign up to set email alerts
|

A lost generation? The financial crisis and the length of working life in Spain

Abstract: Working papers of the Max Planck Institute for Demographic Research receive only limited review. Views or opinions expressed in working papers are attributable to the authors and do not necessarily refl ect those of the Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Second, there is also clear evidence of increases in the average number and length of spells of temporary withdrawal from the labor force (Dudel et al, 2016). This pattern has been observed among individuals who have become unemployed, are not entitled to unemployment benefits, and do not expect to find a job (Congregado et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Second, there is also clear evidence of increases in the average number and length of spells of temporary withdrawal from the labor force (Dudel et al, 2016). This pattern has been observed among individuals who have become unemployed, are not entitled to unemployment benefits, and do not expect to find a job (Congregado et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…A similar problem exists for migration out of Spain: individuals who leave the country are lost to the sample, but may reenter. While it has been shown that this could bias results for females, results for males are affected to a lesser extent (Dudel et al, 2016). For this reason, the working life tables are reported for males only, corrected for the selectivity of the dataset (see below).…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations